Teachers' Perspectives of Creating Storybooks for Primary students - Andanty, Ferra Dian (JET ADI BUANA, 2017)
Storybooks are important materials for teachers in assisting pupils during the teaching learning process in the classroom especially for the young learners because it gives a motivating and meaningful context for language learning. Nowadays, teachers have to be creative and innovative in creating their own storybooks for the teaching learning process. The project of making storybooks had been given to the undergraduate students of 8th semester (2010) at English Language Department, University of PGRI Adi Buana during TEYL (Teaching English to Young Learners) class. Through the results of storybooks project, this research was intended to know whether the undergraduate students' storybooks met the criteria of a good storybook or not. The authors obtained the data from the questionnaires that distributed to ten English teachers in some elementary schools in Surabaya. The result of this research showed that 75% of students' storybooks met the criteria of good storybooks, such as the content is suitable for age level, interesting, memorable, attractive, and easily to understand by children. The result of creating a storybook hopefully will support and help teachers in the teaching learning process in class.